Effects of problem-based learning on EFL learning: a systematic review - Guo, Qian; Jamil, Halimah; Ismail, Lilliati; Luo, Shujie; Sun, Zhubin (Public Library of Science, 2024)
Teaching English as a foreign language (EFL) is a priority globally, but pedagogical methods do not always keep up with the evolving needs of learners. Problem-based learning (PBL) is an innovative pedagogical approach that facilitates students’ self-regulated learning, thereby improving their English proficiency. The present systematic literature review therefore concentrates on the application of PBL methodology in improving students’ English language proficiency. It was conducted according to the systematic review and meta-analysis Preferred Reporting Items for Meta-Analyses (PRISMA) review methodology. In total, 27 articles related to PBL to improve English proficiency published between 2012 and 2023 were identified from Web of Science, Scopus, ProQuest, ERIC, and ScienceDirect databases. In the light of the findings, PBL has a positive effect on students’ behaviour, academic performance, and critical thinking. Consequently, this paper contributes to policy makers, educators, and students to improve the English proficiency of students at all levels of education using PBL approach.